The prevalence and risk factors of diabetes mellitus among tuberculosis patients at Ubuntu clinic, Khayelitsha - Kubjane, Mmamapudi (Institute of Infectious Disease and Molecular Medicine, 2016)
Summary: There is strong evidence suggesting that diabetes mellitus (DM) triples the risk of tuberculosis (TB) disease and worsens TB outcomes. South Africa carries a heavy burden of TB which is primarily driven by the human deficiency virus (HIV). The burden of non-communicable disease is also growing rapidly in South Africa. There is however lack of up to date data on the burden of DM and the associated risk factors among TB patients. This dissertation is based on a cross-sectional study which sought to assess the prevalence of DM and impaired glucose tolerance (IGT) and determine the risk factors associated with DM among TB patients. Methods: This cross sectional study forms part of a case control study that aimed to assess the association between DM and TB and the population attributable risk of TB due to DM in Khayelitsha, a high HIV and TB setting. The TB patients recruited in the case control study formed the population of this current cross-sectional study. Based on oral glucose tolerance test, fasting blood glucose, glycated haemoglobin and self-report the prevalence of DM was determined. Bivariate and multivariate logistic regression analyses were performed to assess risk factors associated DM among TB patients. Due to significant differences between male and females with respect to various characteristics, we also stratified the data by sex during analysis.